2013
DOI: 10.1108/info-07-2013-0039
|View full text |Cite
|
Sign up to set email alerts
|

Dimensioning the elephant: an empirical analysis of the IPv4 number market

Abstract: The elephant in the roomOne of the most important but least-studied aspects of Internet policy is the emergence of a trading market for previously allocated Internet number blocks. Without unique Internet protocol numbers for the networks and devices attached, the Internet simply doesn't work. The original Internet Protocol standard, known as IPv4, specified a 32-bit numbering space, which provided slightly less than 4 billion unique numbers that could be used as addresses (Postel, 1981). A large part of that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A market price for IPv4 number resources encourages conservation and incentivizes the transfer of unused or underused IPv4 numbers to network operators who need them more. Ever since the development and legitimization of secondary markets for IPv4 numbers, market incentives have led to the creation of an increasingly efficient process for locating unused or underused number blocks and for linking buyers and sellers in ways that move numbers from less valued to higher valued uses (Mueller et al, 2013). In addition, network operators can economize on IPv4 addresses by deploying NAT.…”
Section: Supply and Demand For Internet Protocol Version 4 Number Resourcesmentioning
confidence: 99%
“…A market price for IPv4 number resources encourages conservation and incentivizes the transfer of unused or underused IPv4 numbers to network operators who need them more. Ever since the development and legitimization of secondary markets for IPv4 numbers, market incentives have led to the creation of an increasingly efficient process for locating unused or underused number blocks and for linking buyers and sellers in ways that move numbers from less valued to higher valued uses (Mueller et al, 2013). In addition, network operators can economize on IPv4 addresses by deploying NAT.…”
Section: Supply and Demand For Internet Protocol Version 4 Number Resourcesmentioning
confidence: 99%
“…Early academic studies [17,28] discussed the possible implications of market-based mechanisms for reallocating IPv4 addresses. Mueller et al [32,33] used the list of published transfers to analyze the emerging IPv4 transfer market by quantifying the amount of legacy allocations exchanged on the markets and the impact of the need-based policies on the utilization of the transferred blocks. Livadariu et al [23] provided a comprehensive study on the IPv4 transfer market evolution, the exchanged IPv4 blocks, and the impact on the routing table and IPv6 adoption.…”
Section: Ip Transfer Marketmentioning
confidence: 99%
“…Even though ARIN states that legacy holders are subject to ARIN policies, recent transfers, such as the wellknown sale of more than 660K IP addresses from the Nortel bankruptcy to Microsoft, have raised concerns whether they complied with proper ARIN transfer policy. Mueller et al [59] state that while ARIN was formally involved in the transfer, likely no needs-based evaluation was performed on the receiving side, and that ARIN's intervention boiled down to a "face-saving exercise". As the relationship of legacy holders towards the RIRs is not entirely clear, one IP address trader has suggested that legacy address holders in the ARIN region could de-register their address space there and re-register it with a different RIR, such as RIPE [50].…”
Section: Transfers Outside the Rirsmentioning
confidence: 99%